Interoperability and mobility in the future internet - Guimarães, Carlos Eduardo Magalhães (2020)
Research on Future Internet has been gaining traction in recent years, with both evolutionary (e.g., Software Defined Networking (SDN)- based architectures) and clean-slate network architectures (e.g., Information Centric Networking (ICN) architectures) being proposed. With each network architectural proposal aiming to provide better solutions for specific Internet utilization requirements, an heterogeneous Future Internet composed by several architectures can be expected, each targeting and optimizing different use case scenarios. Moreover, the increasing number of mobile devices, with increasing capabilities and supporting different connectivity technologies, are changing the patterns of traffic exchanged in the Internet. As such, this thesis focuses on the study of interoperability and mobility in Future Internet architectures, two key requirements that need to be addressed for the widely adoption of these network architectures. The first contribution of this thesis is an interoperability framework that, by enabling resources to be shared among different network architectures, avoids resources to be restricted to a given network architecture and, at the same time, promotes the initial roll out of new network architectures. The second contribution of this thesis consists on the development of enhancements for SDN-based and ICN network architectures through IEEE 802.21 mechanisms to facilitate and optimize the handover procedures on those architectures. The last contribution of this thesis is the definition of an inter-network architecture mobility framework that enables MNs to move across access network supporting different network architectures without losing the reachability to resources being accessed. All the proposed solutions were evaluated with results highlighting the feasibility of such solutions and the impact on the overall communication.